Cyclohexene oxide mid-chain functional macromonomer of poly(?-caprolactone): Synthesis, characterization, and photoinitiated cationic homo- and copolymerization - Degirmenci, Mustafa; Acikses, Aslisah; Genli, Nasrettin (Wiley, 2012)
In this study, a novel well-defined epoxy mid-chain functional macromonomer of poly(e-caprolactone) (PCL) has been synthesized by ring-opening polymerization (ROP) of e-caprolactone (e-CL) and epoxidation on workup with 3-chloroperoxybenzoic acid. The ROP of e-CL monomer in bulk at 110 degrees C, by means of a dihydroxy functional initiator namely, 3-cyclohexene-1,1-dimethanol in conjunction with stannous-2-ethylhexanoate, (Sn(Oct)2), yielded a well-defined PCL with a cyclohexene mid-chain group. The epoxidation of the cyclohexene (CH) mid-chain group of PCL was performed using 3-chloroperoxybenzoic acid. GPC, IR, and 1H-NMR analyses revealed that a low-polydispersity macromonomer of PCL with the desired cyclohexene oxide (CHO) functionality at the mid-chain was obtained. The photoinduced cationic polymerizations of this macromonomer yielded comb-shaped and graft copolymers. (c) 2011 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: ring-opening polymerization; functionalization of polymers; macromonomers; photopolymerization; graft copolymers